Negative electrode material co-coated with metal nitride and metal oxide, preparation method of negative electrode material, negative electrode and battery

By using a graphite structure co-coated by metal nitride and metal oxide in the negative electrode material of lithium-ion batteries, the problems of reduced capacity and poor cycle stability under high current charging conditions are solved, and high capacity and excellent cycle stability are achieved. And inhibit the formation of lithium dendrites.

CN119447252AActive Publication Date: 2025-02-14CHONGQING INNOVATION CENTER OF BEIJING INSTITUTE OF TECHNOLOGY +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411602906.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-14
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The existing lithium-ion battery negative electrode materials have reduced capacity and poor cycle stability under high current charging conditions, and are prone to lithium dendrites, resulting in safety problems.

Method used

A graphite negative electrode material co-coated with metal nitride and metal oxide is used to form an inorganic rich SEI layer through heat treatment to improve fast charging capacity and inhibit the formation of lithium dendrites.

Benefits of technology

Under high current charging and discharge conditions, high capacity and excellent cycling stability are maintained. The specific capacity under 4C current density is above 220mAh/g, and the capacity retention rate is above 90% after 300 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447252A_ABST
    Figure CN119447252A_ABST
Patent Text Reader

Abstract

The invention relates to the field of lithium ion batteries, and discloses a metal nitride and metal oxide co-coated negative electrode material and a preparation method thereof, a negative electrode and a battery, the metal nitride and metal oxide co-coated negative electrode material comprises graphite and a coating layer, the surface of the graphite is coated with the coating layer, and the coating layer comprises a mixture layer of metal nitride and metal oxide. The negative electrode material provided by the invention shows relatively small polarization, and shows high specific capacity and excellent cycling stability under a large-current charging condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a negative electrode material co-coated with a metal nitride and a metal oxide, a preparation method thereof, a negative electrode and a battery. Background Art

[0002] As a representative of green travel, the scale of electric vehicles is growing day by day. However, problems such as short driving range and slow charging speed restrict the further development of the electric vehicle industry. The fast charging capability of electric vehicles is closely related to the physical and chemical properties of the positive and negative electrode materials of lithium-ion batteries. Graphite negative electrode materials have a lithium storage capacity of about 360mAh / g, but there is a serious polarization phenomenon when facing fast charging conditions, resulting in a lower lithium storage capacity. In addition, under high current charging conditions, lithium dendrites are easily formed on the surface of the graphite electrode, causing battery short circuits and inducing safety problems such as battery fires and explosions.

[0003] The transport process of lithium ions embedded in graphite electrodes mainly includes the following four steps: solvated lithium ions are transported in the electrolyte, solvated lithium ions are desolvated on the electrode surface, lithium ions are transported in the solid electrolyte interface film (SEI film) on the graphite surface, and lithium ions are transported in the graphite bulk phase. Among them, lithium ion desolvation and transport in the SEI film are considered to be the rate-limiting steps. Based on this, the fast charging capability of graphite negative electrode materials can be improved through structural design, such as designing expanded layer, porous or nano-sized graphite negative electrode materials, but the above methods are at the expense of the energy density of graphite negative electrode materials.

[0004] How to maintain high capacity under high current charging conditions and inhibit the formation of lithium dendrites is of great research significance. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems of decreased capacity and poor cycle stability in the negative electrode materials under high current charging conditions in the prior art, and to provide a negative electrode material and a preparation method thereof, a negative electrode and a battery. The negative electrode material provided by the present invention exhibits small polarization, high specific capacity and excellent cycle stability under high current charging conditions.

[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a negative electrode material, which includes graphite and a coating layer, wherein the coating layer is coated on the surface of the graphite, and the coating layer includes a mixture layer of metal nitride and metal oxide.

[0007] The second aspect of the present invention provides a method for preparing a negative electrode material, wherein the preparation method comprises: performing a first reaction on dopamine hydrochloride and graphite in a first solvent to obtain a material I having a surface coated with a polydopamine layer, performing a second reaction on the material I and a metal salt in a second solvent to obtain a material II having a surface coated with a metal salt and a polydopamine layer, performing a first heat treatment on the material II in an ammonia atmosphere to obtain a material III having a surface coated with a metal nitride, and performing a second heat treatment on the material III in an oxygen atmosphere to obtain a negative electrode material having a surface coated with a mixture layer including a metal nitride and a metal oxide;

[0008] The temperature of the first step heat treatment is 500-1000° C., the temperature of the second step heat treatment is 100-500° C., the time is 0.1-1 h, and the volume proportion of ammonia in the ammonia atmosphere is greater than 50%.

[0009] A third aspect of the present invention provides a negative electrode for a lithium ion battery, wherein the negative electrode comprises the negative electrode material described in the first aspect of the present invention or the negative electrode material prepared by the preparation method described in the second aspect of the present invention.

[0010] A fourth aspect of the present invention provides a battery, wherein the battery comprises the negative electrode described in the third aspect of the present invention.

[0011] Through the above technical scheme, the present invention prepares a negative electrode material co-coated with metal nitride and metal oxide, and the metal nitride and metal oxide are in situ converted into an inorganic SEI layer containing metal elements and Li3N and Li2O during the lithiation process, thereby improving the fast charging capability and inhibiting the formation of lithium dendrites under high current charging conditions.

[0012] The negative electrode material prepared by the present invention still has high capacity and excellent cycle stability under high current charge and discharge conditions, the specific capacity at 4C current density is above 220mAh / g, and the capacity retention rate after 300 cycles is above 90%. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 is a SEM image of the negative electrode material prepared in Example 2;

[0014] Figure 2 is the EDS spectrum of the negative electrode material prepared in Example 2;

[0015] Figure 3 is the XRD pattern of graphite and the negative electrode material prepared in Example 5;

[0016] Figure 4 dQ / dV curves corresponding to the first cycle charge and discharge process of graphite and the negative electrode material prepared in Example 7;

[0017] Figure 5 This is a capacity cycle diagram of the negative electrode material prepared in Example 1 at a current density of 4C. DETAILED DESCRIPTION

[0018] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0019] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of this application, unless otherwise specified, "plurality" means two or more.

[0020] In the description of this application, the interface refers to the solid electrolyte interface (SEI) layer, that is, a thin and dense passivation film formed by the reduction and decomposition of solvent molecules and lithium salts in the electrolyte on the surface of the negative electrode material during the charging and discharging process of the lithium-ion battery.

[0021] A first aspect of the present invention provides a negative electrode material, which includes graphite and a coating layer, wherein the coating layer is coated on the surface of the graphite, and the coating layer includes a mixture layer of metal nitride and metal oxide.

[0022] During the lithiation process, the interface of the metal nitride and metal oxide in the coating layer is in situ transformed into an inorganic SEI layer containing metal elements as well as Li3N and Li2O. The lithium ion conductivity of Li3N is higher than that of traditional SEI components, which can accelerate the transmission speed of lithium ions, increase the desolvation speed, realize the rapid transmission of lithium ions at the interface, and improve the fast charging capability. The metal single-substance layer has higher electronic conductivity, which can reduce the interface impedance and weaken the polarization, thereby increasing the lithium nucleation overpotential and inhibiting the formation of lithium dendrites under high current conditions. Constructing a mixture layer of metal nitride and metal oxide can avoid the oxidative decomposition of nitride, which is beneficial to improve the stability of the negative electrode material.

[0023] In some embodiments, preferably, the metal nitride includes Fe4N, and the metal oxide includes Fe2O3. In the coating layer, the metal nitride mainly exists in the form of Fe4N, in addition to which there are small amounts of Fe3N, Fe2N, and Fe6N2. The metal oxide mainly exists in the form of Fe2O3, in addition to which there are small amounts of FeO and Fe3O4.

[0024] In some embodiments, preferably, the coating layer has a thickness of 10-100 nm. The coating layer thickness can be any value between any two of 10 nm, 30 nm, 50 nm, 70 nm, and 100 nm. The coating layer thickness within this range is beneficial to improving the desolvation rate of the negative electrode material and the transmission rate in the SEI film, while effectively inhibiting the formation of lithium dendrites under high current conditions.

[0025] The second aspect of the present invention provides a method for preparing a negative electrode material, wherein the preparation method comprises: performing a first reaction on dopamine hydrochloride and graphite in a first solvent to obtain a material I having a surface coated with a polydopamine layer, performing a second reaction on the material I and a metal salt in a second solvent to obtain a material II having a surface coated with a metal salt and a polydopamine layer, performing a first heat treatment on the material II in an ammonia atmosphere to obtain a material III having a surface coated with a metal nitride, and performing a second heat treatment on the material III in an oxygen atmosphere to obtain a negative electrode material having a surface coated with a mixture layer including a metal nitride and a metal oxide;

[0026] The temperature of the first step heat treatment is 500-1000° C., the temperature of the second step heat treatment is 100-500° C., the time is 0.1-1 h, and the volume proportion of ammonia in the ammonia atmosphere is greater than 50%.

[0027] Material I includes an inner layer of graphite and a polydopamine layer coated on the surface of the graphite, material II includes an inner layer of graphite and a polydopamine layer and a metal salt layer coated on the surface of the graphite, material III includes an inner layer of graphite and a metal nitride layer coated on the surface of the graphite, and the negative electrode material includes an inner layer of graphite and a mixture layer of metal nitride and metal oxide coated on the surface of the graphite.

[0028] In some embodiments, preferably, the metal salt includes one or more of ferric oxalate, ferric sulfate, ferric nitrate and ferric chloride. The metal salt containing the iron element is converted into iron nitride and iron oxide after two-step heat treatment. The iron nitride and iron oxide at the interface are converted into elemental iron, lithium nitride and lithium oxide during the lithiation process. This inorganic-rich fast ion conduction layer is conducive to accelerating the interface ion transport, thereby improving the rate performance of the negative electrode material.

[0029] In some embodiments, preferably, the volume proportion of ammonia in the ammonia atmosphere is greater than 90%. When the volume proportion of ammonia is greater than 50%, it is conducive to the nitridation reaction to generate metal nitrides, and the volume proportion of ammonia can be greater than 50%, 60%, 70%, 80%, 90%, 95%, 99%, etc.

[0030] In some embodiments, preferably, the first step of heat treatment takes 1-4 hours and the heating rate is 1-5°C / min.

[0031] In some embodiments, preferably, the second step heat treatment is performed for 0.1-0.6 h, and the heating rate is 1-5° C. / min.

[0032] During the first step of heat treatment, the metal salt layer coated on the graphite surface is transformed into a metal nitride layer, and polydopamine undergoes thermal decomposition and transforms into an amorphous carbon layer. During the second step of heat treatment, a portion of the metal nitride is transformed into a metal oxide to form a mixture layer of metal nitride and metal oxide. The time of the first step of heat treatment should not be too short, otherwise the metal salt cannot be completely reduced, resulting in incomplete formation of the nitride layer. The time of the second step of heat treatment should not be too long to avoid the complete conversion of the metal nitride into a metal oxide. The heating rate of the two-step heat treatment is in the range of 1-5℃ / min, which is conducive to the complete reaction.

[0033] The temperature of the first step heat treatment can be any value between any two of 500℃, 550℃, 600℃, 650℃, 700℃, 750℃, 800℃, 850℃, 900℃, and 1000℃; the time can be any value between any two of 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, and 4h; the heating rate can be any value between any two of 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min, and 5℃ / min. The temperature of the second step heat treatment can be any value between any two numbers of 100℃, 120℃, 150℃, 180℃, 200℃, 300℃, 400℃, and 500℃; the time can be any value between any two numbers of 0.1h, 0.2h, 0.3h, 0.4h, 0.6h, 0.8h, and 1h; the heating rate can be any value between any two numbers of 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min, and 5℃ / min.

[0034] In some embodiments, preferably, the mass ratio of dopamine hydrochloride to graphite is 0.01-0.3. By constructing a polydopamine layer on the graphite surface, the adsorption capacity between graphite and metal salt can be significantly improved, which helps to construct a uniformly coated metal salt layer. The mass ratio of dopamine hydrochloride to graphite can be any value between any two numbers of 0.01, 0.05, 0.1, 0.15, 0.2, 0.25, and 0.3. The mass ratio of dopamine hydrochloride to graphite is conducive to forming a uniform polydopamine layer on the graphite surface within this range, thereby forming a uniform metal salt layer.

[0035] In some embodiments, preferably, the mass ratio of the metal salt to the graphite is 0.01-0.5. The mass ratio of the metal salt to the graphite can be any value between any two of 0.01, 0.1, 0.2, 0.3, 0.4, and 0.5. The mass ratio of the metal salt to the graphite within this range is conducive to forming a metal nitride and metal oxide mixture layer uniformly coated on the graphite surface. When the mass ratio of the metal salt to the graphite is too high, the coating layer formed is too thick, which is not conducive to the transmission of lithium ions, but leads to a decrease in the rate performance of the negative electrode material.

[0036] In some embodiments, preferably, the regulator for adjusting the pH value of the first reaction is ammonia water and / or Tris solution.

[0037] In some embodiments, preferably, the pH value of the first reaction is 8 to 9. A pH value of 8 to 9, especially about 8.5, is conducive to the polymerization of dopamine molecules to form polydopamine.

[0038] The pH value of the first reaction can be any value between any two of 8, 8.2, 8.4, 8.5, 8.7, and 9.

[0039] In some embodiments, preferably, the first reaction process includes: first stirring the dopamine hydrochloride, graphite and the first solvent.

[0040] In some embodiments, preferably, the first stirring time is 12-36 hours.

[0041] The dopamine hydrochloride and graphite are uniformly dispersed by stirring to form a uniformly coated polydopamine layer. The first stirring time can be any value between any two of 12h, 16h, 20h, 24h, 28h, 32h, and 36h.

[0042] In some embodiments, preferably, the second reaction process includes: mixing the material I, the metal salt and the second solvent and heating until the second solvent is evaporated to dryness, thereby forming the material II having the metal salt and the polydopamine layer coated on the surface.

[0043] In some embodiments, preferably, the mixing process comprises: subjecting the material I, the metal salt and the second solvent to ultrasonic treatment, and then performing the second reaction under a second stirring condition.

[0044] Material I and the metal salt are uniformly dispersed in the second solvent by ultrasound and second stirring, and the second solvent is gradually evaporated by heating. During the evaporation process, the metal salt gradually coats the surface of material II to form a uniform metal salt layer.

[0045] The first solvent may be deionized water, and the second solvent may be deionized water.

[0046] A third aspect of the present invention provides a negative electrode for a lithium ion battery, wherein the negative electrode comprises the negative electrode material described in the first aspect of the present invention or the negative electrode material prepared by the preparation method described in the second aspect of the present invention.

[0047] A fourth aspect of the present invention provides a battery, wherein the battery comprises the negative electrode described in the third aspect of the present invention.

[0048] According to a particularly preferred embodiment of the present invention, dopamine hydrochloride and graphite are first stirred in a first solvent to obtain a material I having a surface coated with a polydopamine layer, wherein the mass ratio of dopamine hydrochloride to graphite is 0.2-0.3, the pH of the first stirring is 8.4-8.6, the pH adjuster is ammonia water, and the first stirring time is 20-25h;

[0049] The material I, the metal salt and the second solvent are subjected to ultrasonic treatment, and then heated under a second stirring condition until the second solvent is evaporated to dryness, to obtain the material II having the metal salt and the polydopamine layer coated on the surface, wherein the metal salt is ferric oxalate, and the mass ratio of the metal salt to the graphite is 0.18-0.22;

[0050] The material II is subjected to a first step heat treatment in an ammonia atmosphere to obtain a material III whose surface is coated with a metal nitride, and the material III is subjected to a second step heat treatment in an oxygen atmosphere to obtain a negative electrode material whose surface is coated with a mixture layer including a metal nitride and a metal oxide, wherein the volume proportion of ammonia in the ammonia atmosphere is greater than 95%, the temperature of the first step heat treatment is 550-650°C, the time is 2-4h, and the heating rate is 3-5°C / min, and the temperature of the second step heat treatment is 120-180°C, the time is 0.3-0.6h, and the heating rate is 3-5°C / min.

[0051] The negative electrode material prepared by this scheme maintains a high specific capacity of not less than 300 mAh / g at a current density of 4C, and the capacity retention rate after 300 cycles at a current density of 4C is not less than 98%, preferably 100%, and the capacity retention rate after 500 cycles exceeds 90%.

[0052] The present invention will be described in detail below through examples. In the following examples, the scanning electron microscope (SEM) image of the negative electrode material is obtained by scanning electron microscope testing, the EDS energy spectrum is obtained by scanning electron microscope testing, and the X-ray diffraction (XRD) image is obtained by X-ray diffractometer testing. The dQ / dV curve corresponding to the first week of charge and discharge and the capacity cycle diagram at 4C current density are obtained by charging and discharging the assembled battery with a battery tester.

[0053] Example 1

[0054] 0.25 g of dopamine hydrochloride and 1 g of natural graphite were dissolved in 100 mL of water, and the mixture was uniformly dispersed by the first stirring at a rotation speed of 400 rpm. Ammonia water was added to adjust the pH value to 8.5. After stirring for 24 h, the mixture was washed with deionized water and ethanol alternately by suction until the pH value was neutral. The powder was collected and vacuum dried at 60 ° C for 12 h to obtain material I.

[0055] All of the above material I and 0.2 g of ferric oxalate were dissolved in 20 mL of deionized water, ultrasonicated for 30 min, heated until the deionized water was evaporated under the second stirring state, the second stirring speed was 400 rpm, the heating temperature was 80°C, and then dried in an oven at 80°C for 4 h to obtain material II.

[0056] Material II was subjected to a two-step heat treatment. The first step of heat treatment was carried out in an ammonia atmosphere, in which the volume proportion of ammonia was 99%. The temperature was increased to 800°C at a heating rate of 5°C / min and kept warm for 3 hours, then cooled. The second step of heat treatment was carried out in an oxygen atmosphere, in which the temperature was increased to 150°C at a heating rate of 5°C / min and kept warm for 0.5 hours, then cooled to obtain a negative electrode material co-coated with metal nitride and metal oxide, in which the metal nitride was mainly Fe4N and the metal oxide was mainly Fe2O3.

[0057] Example 2

[0058] The method of Example 1 was followed, except that: the amount of dopamine hydrochloride added was 0.15 g, that is, the mass ratio of dopamine hydrochloride to graphite was 0.15; ferric nitrate was used instead of ferric oxalate, and the amount of ferric nitrate added was 0.5 g, that is, the mass ratio of metal salt to graphite was 0.5; and the temperature of the first step heat treatment was 800°C.

[0059] The negative electrode materials of Examples 1-16 and Comparative Examples 1-6 have similar SEM images and EDS spectra. Example 2 is representative, and its SEM image is as follows: Figure 1 As shown in the figure, the surface of the negative electrode material is smooth, there is no obvious particle aggregation, and the particle size is about 10μm. The EDS spectrum of the negative electrode material is shown in the figure Figure 2 As shown, it shows that the surface of the negative electrode material contains Fe, C, O, and N elements and they are evenly distributed.

[0060] Example 3

[0061] The method of Example 2 was followed, except that the amount of dopamine hydrochloride added was 0.3 g, that is, the mass ratio of dopamine hydrochloride to graphite was 0.3.

[0062] Example 4

[0063] The method of Example 2 was followed, except that the amount of dopamine hydrochloride added was 0.05 g, that is, the mass ratio of dopamine hydrochloride to graphite was 0.05.

[0064] Example 5

[0065] The method of Example 2 was followed, except that the amount of ferric nitrate added was 0.2 g, that is, the mass ratio of the metal salt to the graphite was 0.2.

[0066] The negative electrode materials of Examples 1-16 have similar XRD patterns, with Example 5 being representative. The XRD patterns of graphite and the negative electrode material prepared in Example 5 are as follows: Figure 3 As shown, in addition to the diffraction peaks of the graphite body, there are also diffraction peaks of iron oxide (Fe2O3) and iron nitride (Fe4N), proving that a mixed coating layer of iron oxide and iron nitride is formed on the graphite surface, while such diffraction peaks do not exist in the graphite itself.

[0067] Example 6

[0068] The method of Example 2 was followed, except that the amount of ferric nitrate added was 0.05 g, that is, the mass ratio of the metal salt to the graphite was 0.05.

[0069] Example 7

[0070] The method of Example 5 is followed, except that the temperature of the first heat treatment step is 1000°C.

[0071] Example 8

[0072] The method of Example 5 is followed, except that the temperature of the first heat treatment step is 600°C.

[0073] Example 9

[0074] The method of Example 5 was followed, except that the first step of heat treatment lasted for 1 h and the heating rate was 1°C / min.

[0075] Example 10

[0076] The method of Example 5 was followed, except that the temperature of the second step heat treatment was 300°C and the heating rate was 3°C / min.

[0077] Embodiment 11

[0078] The method of Example 5 was followed, except that the temperature of the second step heat treatment was 500°C, the time was 0.1 h, and the heating rate was 1°C / min.

[0079] Example 12

[0080] The method of Example 5 was followed, except that the time for the second heat treatment was 1 h.

[0081] Example 13

[0082] The method of Example 2 was followed, except that Tris solution was used instead of ammonia water, and the first stirring time was 12 h.

[0083] Embodiment 14

[0084] The method of Example 2 was followed, except that the first stirring time was 36 h.

[0085] Embodiment 15

[0086] The method of Example 2 was followed, except that the amount of dopamine hydrochloride added was 0.5 g, that is, the mass ratio of dopamine hydrochloride to graphite was 0.5.

[0087] Example 16

[0088] The method of Example 2 was followed, except that the amount of ferric nitrate added was 0.7 g, that is, the mass ratio of the metal salt to the graphite was 0.7.

[0089] Comparative Example 1

[0090] The method of Example 5 was followed, except that the temperature of the first step heat treatment was 200°C, the time was 4 hours, and the heating rate was 3°C / min.

[0091] Comparative Example 2

[0092] The method of Comparative Example 1 was followed, except that the temperature of the first heat treatment step was 80°C.

[0093] Comparative Example 3

[0094] The method of Example 5 was followed, except that the temperature of the second heat treatment was 50°C.

[0095] Comparative Example 4

[0096] The method of Example 11 is followed, except that the temperature of the second heat treatment is 650°C.

[0097] Comparative Example 5

[0098] The method of Example 5 was followed, except that the time for the second heat treatment was 2 h.

[0099] Comparative Example 6

[0100] The method of Example 1 is followed, except that the volume proportion of ammonia in the ammonia atmosphere is 30%.

[0101] Test Example 1

[0102] The negative electrode materials prepared in Examples 1-16 and Comparative Examples 1-6 were prepared into battery negative electrodes and further assembled into button batteries for electrochemical testing. The LB315 electrolyte used was 1 mol / L LiPF6 dissolved in a mixed solution of ethylene carbonate and diethyl carbonate, wherein the mass ratio of ethylene carbonate to diethyl carbonate was 7:3.

[0103] The first week charge and discharge test was carried out at a temperature of 25°C and a voltage window of 0.01-1.5V at a current density of 0.1C (1C = 300mAh / g), and the dQ / dV curves corresponding to the first week charge and discharge process of graphite and negative electrode materials were obtained. Examples 1-16 have similar dQ / dV curves corresponding to the first week charge and discharge process. Taking Example 7 as an example, its dQ / dV curve is as follows: Figure 4 As shown. The positive region is the charging process, the negative electrode undergoes a reduction reaction, and the corresponding peak is the reduction peak. The negative region is the discharging process, the negative electrode undergoes an oxidation reaction, and the corresponding peak is the oxidation peak. As can be seen from the figure, compared with unmodified graphite, the negative electrode material co-coated with iron nitride and iron oxide has a higher reduction potential and a lower oxidation potential, indicating that the negative electrode material has a weaker polarization, which is conducive to the performance of rate performance and inhibits the formation of lithium dendrites.

[0104] The capacity cycle diagram of the negative electrode material prepared in Example 1 at a current density of 4C is shown in FIG. Figure 5 As shown, the specific capacity of the negative electrode material co-coated with iron nitride and iron oxide at a current density of 4C is 300mAh / g, while the graphite body can only exert a specific capacity of about 100mAh / g. In addition, the capacity retention rate of the negative electrode material after 300 cycles at a current density of 4C is 100%.

[0105] The electrochemical performance of Examples 1-16 and Comparative Examples 1-6 was tested at a temperature of 25° C., a voltage window of 0.01-1.5 V, and a current density of 4 C. The results are shown in Table 1.

[0106] Table 1 Specific capacity and capacity retention rate of negative electrode materials at 4C current density

[0107] Example Specific capacity before cycle test / mAh / g Capacity retention rate after 300 cycles / % Example 1 300 100 Example 2 320 95 Example 3 280 98 Example 4 340 93 Example 5 300 95 Example 6 290 90 Example 7 250 95 Example 8 220 90 Example 9 240 95 Example 10 220 90 Embodiment 11 250 95 Example 12 250 95 Example 13 300 95 Embodiment 14 300 95 Embodiment 15 280 95 Example 16 280 95 Comparative Example 1 150 90 Comparative Example 2 100 80 Comparative Example 3 100 80 Comparative Example 4 180 90 Comparative Example 5 150 80 Comparative Example 6 100 80

[0108] It can be seen from the results in Table 1 that the negative electrode material prepared by the present invention has higher specific capacity and capacity retention rate than unmodified graphite under high current charging conditions. Compared with Example 2, the capacity retention rate of the negative electrode materials prepared in Examples 3, 4, and 15 shows a trend of first increasing and then decreasing, and the specific capacity of the negative electrode materials prepared in Examples 5, 6, and 16 shows a trend of first increasing and then decreasing. This is because when the mass ratio of dopamine hydrochloride to graphite is too large, or the mass ratio of metal salt to graphite is too large, a thick coating layer will be formed on the surface of the negative electrode material, which hinders the effective transmission of lithium ions, resulting in a decrease in the specific capacity or cycle stability of the material.

[0109] Compared with Example 5, the specific capacity and capacity retention rate of the negative electrode materials prepared in Comparative Examples 1 and 2 are reduced. This is because the temperature of the first step heat treatment is too low, and the metal salt layer cannot be effectively converted into a metal nitride layer. Compared with Example 5, the specific capacity and capacity retention rate of the negative electrode material prepared in Comparative Example 3 are reduced. This is because the temperature of the second step heat treatment is too low, and the metal nitride layer cannot be effectively converted into a metal oxide layer. The specific capacity and capacity retention rate of the negative electrode material prepared in Comparative Example 4 are slightly lower than those in Example 11. This is because the temperature of the second step heat treatment in Comparative Example 4 is relatively high, resulting in more nitride layers being converted into oxide layers, reducing the interfacial lithium ion transmission capacity, reducing the interface stability, and reducing the specific capacity and capacity retention rate of the negative electrode material. The specific capacity of the negative electrode material prepared in Comparative Example 5 is significantly reduced compared with Example 5. This is because the second step heat treatment time is extended in Comparative Example 5, resulting in the proportion of the nitride layer on the surface of the negative electrode material being converted into an oxide layer exceeding the acceptable range, reducing the interfacial ion transmission, and having an adverse effect on the performance of the material, indicating that the time for the second step heat treatment needs to be strictly controlled. The specific capacity and capacity retention rate of the negative electrode material prepared in Comparative Example 6 are much lower than those in Example 1. This is because in Comparative Example 6, during the first step of heat treatment, the volume proportion of ammonia in the ammonia atmosphere is 30%, indicating that it is necessary in the present invention that the volume proportion of ammonia in the ammonia atmosphere is greater than 50%.

[0110] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A negative electrode material, characterized in that: The invention comprises graphite and a coating layer, wherein the coating layer is coated on the surface of the graphite and comprises a mixture layer of metal nitride and metal oxide.

2. The negative electrode material according to claim 1, wherein The metal nitride includes Fe4N, and the metal oxide includes Fe2O3.

3. The negative electrode material according to claim 1 or 2, wherein The coating layer has a thickness of 10-100 nm.

4. A method for preparing a negative electrode material, characterized in that: The preparation method comprises: performing a first reaction on dopamine hydrochloride and graphite in a first solvent to obtain a material I having a surface coated with a polydopamine layer, performing a second reaction on the material I and a metal salt in a second solvent to obtain a material II having a surface coated with a metal salt and a polydopamine layer, performing a first heat treatment on the material II in an ammonia atmosphere to obtain a material III having a surface coated with a metal nitride, and performing a second heat treatment on the material III in an oxygen atmosphere to obtain a negative electrode material having a surface coated with a mixture layer including a metal nitride and a metal oxide; The temperature of the first step heat treatment is 500-1000° C., the temperature of the second step heat treatment is 100-500° C., the time is 0.1-1 h, and the volume proportion of ammonia in the ammonia atmosphere is greater than 50%.

5. The preparation method according to claim 4, wherein The metal salt includes one or more of ferric oxalate, ferric sulfate, ferric nitrate and ferric chloride; And / or, the volume proportion of ammonia in the ammonia atmosphere is greater than 90%; And / or, the first step of heat treatment is performed for 1-4 hours at a heating rate of 1-5°C / min; And / or, the second step heat treatment time is 0.1-0.6h, and the heating rate is 1-5°C / min; And / or, the mass ratio of dopamine hydrochloride to graphite is 0.01-0.3; And / or, the mass ratio of the metal salt to the graphite is 0.01-0.

5.

6. The preparation method according to claim 4 or 5, wherein: The pH value of the first reaction is 8-9; Preferably, the regulator for adjusting the pH value of the first reaction is ammonia water and / or Tris solution.

7. The preparation method according to any one of claims 4 to 6, wherein: The process of the first reaction includes: first stirring the dopamine hydrochloride, graphite and the first solvent; Preferably, the first stirring time is 12-36 hours.

8. The preparation method according to any one of claims 4 to 7, wherein: The second reaction process includes: mixing the material I, the metal salt and the second solvent and heating until the second solvent is evaporated to dryness, thereby forming the material II with the metal salt and the polydopamine layer coated on the surface.

9. A negative electrode of a lithium ion battery, characterized in that: The negative electrode comprises the negative electrode material described in any one of claims 1 to 3 or the negative electrode material prepared by the preparation method described in any one of claims 4 to 8.

10. A battery, characterized in that: The battery comprises the negative electrode according to claim 9.

Citation Information

Patent Citations

  • Preparation method for core-shell type carbon-coated iron nitride nano-composite particles and application of core-shell type carbon-coated iron nitride nano-composite particles

    CN102623696A

  • Transition metal nitride / nitrogen-doped graphene nanometer composite material and preparation method and application thereof

    CN107610938A

  • Coated graphite lithium ion battery negative electrode material and preparation method thereof

    CN108305994A

  • A copper nitride modified lithium battery material, a preparation method and an application thereof

    CN109216675A

  • Carbon-doped metal nitride prepared by urea and method thereof

    CN110292943A